Nutrient management study on tartary buckwheat in Dolakha condition of Nepal - Baral, Bandhu Raj; Subedi, Subash; Adhikari, Jagat Bandhu; Gurung, Suk Bahadur; Dhami, Narayan Bahadur (Nepal Agriculture Research Journal, 2025)
Buckwheat (Fagopyrum spp) is a sixth staple food crop in Nepal. It’s productivity is low in Nepal as compared to other countries. One of the factors of low productivity is poor nutrient management. A field experiment was carried out to study the effect of nutrient management on grain yield of tartary buckwheat at Hill Crops Research Program, Kabre, Dolakha. The field experiment consists of seven fertilizer treatments with different nutrient combination doses, replicated thrice and laid out in randomized complete block design. The tested variety was Tite Phapar-1 and experiments were conducted during 2019, 2020 and 2022. Seven fertilizer treatments were FYM 5 t ha-1, 30:30:30 N:P2O5:K2O kg ha-1, 30:60:30 N:P2O5:K2O kg ha-1, 60:30:30 N:P2O5:K2O kg ha-1, 60:60:30 N:P2O5:K2O kg ha-1, 90:30:30 N:P2O5:K2O kg ha-1 and 90:60:30 N:P2O5:K2O kg ha-1, respectively. The results of the experiment showed that grain yield, no. of flower cluster per plant, no. of seeds per cyme were significantly affected by nutrient doses. Tite Phapar-1 variety of buckwheat produced the highest grain yield (2.05 t ha-1) when applied 90:30:30 N:P2O5:K2O kg ha-1 followed by 60:60:30 N:P2O5:K2O kg ha-1 (1.754 t ha-1) and 60:30:30 N:P2O5:K2O kg ha-1 (1.74 t ha-1). Among these three nutrient doses, there was no significant different on grain yield. Therefore, it was concluded that 60:30:30 N: P2O5:K2O kg ha-1 could be recommended for Tite Phapar-1 cultivation under Kabre, Dolakha condition and similar soil types and ecology of Nepal.